Review on Computational Chemistry in Drug Discovery - G. Hemalatha (AG Volumes, 2025)
By assisting pharmaceutical scientists and medicinal chemists in the creation of new, safe therapeutic ideas via the logical design and placement of current medicines, computational techniques help reduce the necessity for animal medical research. Examine the many studies on computational approaches in drug development that have been published in this article. According to this study, computational chemistry has transformed modern drug discovery by offering strong tools and techniques for predicting and examining molecular interactions. Drug development has been greatly expedited by computer approaches, from virtual screening to lead optimisation and toxicity prediction. Molecular docking, pharmacophore modelling, MD simulations, QSAR, and virtual screening are some of the computational chemistry technologies that are used to identify drug candidates with potential bioactivities. In order to improve the drug development process, these methods should be able to describe molecules that are effective, target-selective, and absorbable. New possibilities for creativity in drug discovery are presented by recent developments in AI, ML, and high-performance computers, which further expand the potential of computational chemistry.